Eficiência do polímero hidroabsorvente na produção de mudas de maracujazeiro-amarelo sob estresse hídrico - Araújo, Vanderléia Fernanda dos Santos (2020)
Passion fruit is one of the most produced fruits in Brazil. However, its cultivation under water stress conditions promotes negative effects that can affect all vegetative stages. The production of good quality seedlings depends mainly on the availability of water, that is, a limiting factor in semiarid regions. The use of the hydro-absorbent polymer is a strategy to retain water in the soil and reduce nutrient leaching. With this, the objective was to evaluate the influence of the application of doses of absorbent polymers in yellow passion fruit seedlings cultivated in two types of soil, with and without water stress. A research was carried out in a greenhouse, at the Center for Agronomic and Environmental Sciences (CCAA) of UEPB, Campus II, located in the municipality of Lagoa Seca-PB. The experiment consisted of 20 controls, applying the factor 2x2x5, referring to two substrates with Neossolo Regolitco and Neossolo Flúvico soils, two water conditions (with and without stress, 40% and 80% of equal field capacity) and five doses of hydrogen . absorbent polymer (0.0, 1.25, 2.5, 3.75 and 5.0 g L^-1), with four replications, resulting in 80 plots. Plant growth and physiological tests were performed. The data obtained were taxed as to normality. Then, they were submitted to analysis of variance by the F test, with a 5% probability. Qualitative and quantitative factors were analyzed using the Tukey test, at 5% and regression analysis, respectively. The software used was SISVAR. The data were also used for principal component analysis (ACP). A condition of water stress with maintenance of 40% of the field capacity was not mitigated by the application of hydrogel, reducing the growth of passion fruit seedlings grown on the two substrates. The hydrogel applied in the condition without water stress increased the growth of passion fruit seedlings grown in both soils. As physiological variables in general, they evidenced the effects of water stress on yellow passion fruit seedlings, regardless of the applied hydrogel doses. An ACP that did not demonstrate RR with a dose more correlated with growth was 5 g L^-1 of hydrogel. And in RY, the best dose was 3.75 g L^-1 in the same variables.